The Dominant locus of control in Team and individual sports : a comparative study - قارة سعيد (sports creativity, 2025)
The study dealt with: Dominant locus of control in Team and individual sports - a comparative study. By answering the following questions: What is the dominant locus of control in team sports ? What is the dominant locus of control in individual sports ? - - Is there a relationship between locus of control and commitment to sport practice in team and individual sports ?, The study sample consisted of 80 players (team and individual sports), they were asked to respond to the locus of control scale, the study was conducted using the descriptive approach, and results were concluded that the dominant locus of control in team sports is the external dimension, and the dominant dimension in individual sports is the internal dimension. - The existence of a relationship between the Internal locus of control and the commitment to sport practice among individual sports